328. National Expertise Group to Improve Management of Complex Encephalitis Cases. (26th November 2018) - Stahl, Jean-Paul; De Broucker, Thomas; Alain, Sophie; Epaulard, Olivier; Herrmann, Jean Louis; Honnorat, Jerome; Mailles, Alexandra; Martinez-Almoyna, Laurent; Morand, Patrice; Sonneville, Romain; Tattevin, Pierre
Abstract: Background: Incidence of infectious encephalitis in France is evaluated to be 0.5 to 1/100, 000 inhabitants. That means encephalitis are rare infections, and not all physicians do not have expertise about this disease. In case of complex presentations, they may benefit from advices and guidance from a multidisciplinary group. The French infectious diseases society implemented a group of expertise in 2016 to address clinicians' difficulties with complex cases in a timely manner. Methods: Experts were delegated by scientific societies (Infectious Disease, Microbiology, Neurology, Intensive care and Public Health) with regards to their expertise in brain infections. Any physician facing difficulties to manage a patient presenting as a complex case can ask for advice, using a specific e-mail address ( encephalite.spilf@infectiologie.com ). They have to provide a detailed summary of the clinical case, together with all available biological and etiological results and, when possible, an access to brain images. The case file is then or circulated by mail or discussed in a conference call, within 48 hours. At the end of the discussion, a written answer is produced (detailed recommendations and justification). The traceability of the advice is kept by the French infectious diseases society for both teaching purposes and legal matters. Results: So far we had to examine 32 cases, providing from various hospital in mainland France, French West Indies, and Polynesia: 15 from university hospital and 17 from nonuniversity hospitals. Questions (overlapping in some cases) were related to diagnosis procedure (12), to treatment (4), to interpretation of imaging (5), to management of failure (6), and interpretation of test results (10). Our answers were: investigation for autoimmune or inflammatory disease (15); investigation for tuberculosis and/or treatment (14); investigation for tumour (3); complementary tests for an unusual pathogen (10). Pertinence of the advices was adapted in 20 cases (30 evaluated). Conclusion: Such a group seems to be useful, and the organization at a national-level works. It is also the opportunity to extend our network in the field of neurological infections, and to use the submitted cases as education material for young ID fellows. Disclosures: All authors: No reported disclosures.